Association of genetic variation in tumor necrosis factor-α gene with susceptibility to rheumatoid arthritis in southern Iraq - Sara H. Jabbar, (University of Thi-Qar Journal of Science, 2023)
: Rheumatoid arthritis is the most commonly occurring systemic autoimmune disease caused by genetic, epigenetic, and environmental factors. It affects 0.5-1% of the worldwide population and increases in incidence with age. Tumor necrosis factor-α, major candidate gene in the pathogenesis of RA. Gene polymorphisms occurring in this pro-inflammatory cytokine may increase the risk of RA. This study aimed to evaluate the association between polymorphisms in TNF-α gene at location -308(rs1800629), -238(rs361525) and -376(1800750) (G/A) and RA susceptibility. The study also evaluated the effects of these polymorphisms on their corresponding gene levels in serum.Methods: This case-control study was conducted on 49 individuals (30 RA patients and 19 age- and sex-matched healthy volunteers as controls). Genomic DNA extracted from all participant blood, then amplified by PCR and genotyped by sequencing.Additionally, the serum level of TNF-α was quantified using an enzyme-linked immunosorbent assay (ELISA).Results: The results showed that thehomozygosity for the TNF-α -308 G allele significantly act as a genetic factor associated with increased RA risk (p = 0.029, OR: 4.727, 95%CI: 1.175–19.016). The A allele of -238 and -376 polymorphisms may act as a possible risk factor for RA (OR: 7.63, 95%CI:0.409-14.07; OR:6.13, 95%CI:.0.32-11.214). However, no significant differences were observed.Conclusion: The GG genotype ofTNF-α -308 SNP associated with increased rheumatoid arthritis risk.